Strategic technology alternatives for a start-up management and technology consulting firm a case study - Lamug, Ann Ruth P.
The focus of this project is a start-up transitional venture from an established parent company that is deeply entrenched in major industries across several countries. The new firm faces unique business and technology challenges at start-up. This technology consulting company is a novel albeit a veering-away from the parent company's traditional business ventures. This legacy carries with it both an advantage and a burden. This dichotomy is thoroughly discussed in this paper. The proposed strategic alternatives for the start-up firm are a result of careful research centered on technology intelligence activities : performance of environment scanning, analysis of forecasts in the technology services industry, and impact assessment. It explores trends in international technology transfer of services and the diversity of national environments associated with increased technological learning and greater revenue potential. A comparative study was also conducted to present the cases of firms that have undergone the same challenges at start-up. The project presents and contrasts the traditional business strategies with technology management strategies as proposed for the firm in focus. Implementation approaches for the proposed strategies are also presented.